An Action for Determination Within the Meaning of Art. 189 C.C.P, and the Development of Polish Case-Law Concerning the Legal Aspects of Gender Reassignment - Fibinger-Jasińska, Justyna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The issue of gender reassignment remains a controversial topic both morally and customly, philosophically and medically intricate. However, without going into these issues, which of course should not be underestimated and in fact should take the lead, it is worth looking at the legal aspect of gender reassignment, above all through the prism of the development of Polish case law in this area. The emphasis on the evolution of the jurisprudence in this matter remains all the more important because the Polish law has not seen a direct regulation of the indicated matter in the provisions of substantive law, and only the auxiliary use of the institution specified in Article 189 of the Code of Civil Procedure allows, in the current state of the law, the use of an action for determination as a procedural institution that allows for the legal determination of gender, in accordance with gender identity.